Acculturation and suicidal ideation among Turkish migrants in the Netherlands✰. (May 2019) - Eylem, Ozlem; Dalḡar, İlker; İnce, Burçin Ünlü; Tok, Firdevs; van Straten, Annemieke; de Wit, Leonore; Kerkhof, Ad.J.F.M.; Bhui, Kamaldeep
Highlights: Turkish migrants who actively participate in the host culture may have a lower risk of developing suicidal thinking. Greater cultural maintenance might hinder social adaptation leaving Turkish migrants more prone to hopelessness for their future, and suicidal thinking. The variations in acculturation experiences could be related with attachment styles. The assessment of acculturation and attachment styles may be useful in identifying high risk profiles of migrants. More attention and prominence should be given to acculturation in migrants in general, and further understanding on how it leads to suicidal behaviours specifically. Abstract: More suicidal ideation and higher rates of attempted suicide are found in Turkish people when compared with the general population in Europe. Acculturation processes and related distress may explain an elevated risk of suicide. The current study investigates the association between acculturation and suicidal ideation among Turkish migrants in the Netherlands. The mediating effect of hopelessness and moderating effect of secure attachment are also examined. A total of 185 Turkish migrants living in the Netherlands were recruited through social media and through liaison with community groups. They completed an online survey including validated measures of suicidal ideation, hopelessness, acculturation and attachment style. Mediation and moderation analyses were tested using bootstrapping. Higher participation was associated with less hopelessness and less suicidal ideation. Greater maintenance of one's ethnic culture was associated with higher hopelessness and higher suicidal ideation. Greater participation was associated with less suicidal ideation particularly amongst those with less secure attachment styles. Turkish migrants who participate in the host culture may have a lower risk of developing suicidal thinking. Participation may protect against suicidal thinking, particularly among those with less secure attachment styles.